2021
DOI: 10.1002/ep.13728
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of palm oil products as electrical insulating medium in oil‐immersed transformers

Abstract: The physico-chemical and electrical insulating properties of certain palm oil products, including triglyceride oils, fatty acids, fatty esters, and glycerol were evaluated for use in oil-immersed transformers. The studied triglyceride oils have excellent kinematic viscosity values: 30.25-40.49 mm 2 s À1 at 40 C, 6.46-8.34 mm 2 s À1 at 100 C; flash point: 278-320 C; moisture content: 16-175 mg kg À1 and dielectrical breakdown voltage: 29.1-40.9 kV. Fatty acids and fatty esters have relatively lower kinematic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…5 and Table II depict various ACBDV results of PO by various researchers that used 2.5 mm gap distances of electrodes as a benchmark. Mohd N. K. et al [73] compared the ACBDV of RBDPO olein, RBDPKO, and CPO, where it was figured out that CP obtained the highest ACBDV value, followed by RBDPO olein and RBDPKO. However, experimental findings demonstrated that RBDPO olein, after being blended with oleic acid (OA), produces the highest ACBDV compared to other PO samples.…”
Section: ) Ac Breakdown Voltage Of Palm Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…5 and Table II depict various ACBDV results of PO by various researchers that used 2.5 mm gap distances of electrodes as a benchmark. Mohd N. K. et al [73] compared the ACBDV of RBDPO olein, RBDPKO, and CPO, where it was figured out that CP obtained the highest ACBDV value, followed by RBDPO olein and RBDPKO. However, experimental findings demonstrated that RBDPO olein, after being blended with oleic acid (OA), produces the highest ACBDV compared to other PO samples.…”
Section: ) Ac Breakdown Voltage Of Palm Oilmentioning
confidence: 99%
“…However, only a few studies have found that the results of fire points exceed the limit. Senthilkum et al [180] and Aditama et al [181] studied the flash point of RBDPO and obtained high flash point values of 320 o C and 424 o C. Mohd et al [73] compared the flash point and fire points of several types of RBDPO with and without additives. It was discovered that RBDPO without any additives has a significant flash point and fire points that also exceed 300 o C temperature.…”
Section: Flash Point and Fire Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of triglycerides to methyl ester appeared to be the primary cause of the viscosity reduction. Low viscosity transformer oils are preferred because they promote heat transfer and circulation (Mohd et al, 2021;Walvekar et al, 2022). NPs employed increased, the water content of their NF decreased.…”
Section: Physicochemical Characterisationmentioning
confidence: 99%
“…To find out the performance of palm oil, it is necessary to conduct research using pure palm oil. Palm oil has a kinematic viscosity value between 30.25 to 40.49 mm 2 /s at 40 o C, the breakdown voltage is from 29.1 kV to 40.9 kV, and the moisture content of 16 to 175 mg/kg [18]. For the breakdown voltage and water content results, some values have met and have not met the requirements, so further improvements need to be made to achieve a value like the standard mineral oil.…”
Section: Introductionmentioning
confidence: 99%